2016
DOI: 10.1007/s40692-016-0064-3
|View full text |Cite
|
Sign up to set email alerts
|

The link between achievement emotions, appraisals, and task performance: pedagogical considerations for emotions in CBLEs

Abstract: Achievement emotions have a powerful influence on how students interact with current and future learning and performance tasks. As such, pedagogical practices that support adaptive student emotions are critical for teaching and learning in computer-based learning environments (CBLEs). This research investigates the relationship between during-task achievement emotions and participants' appraisals of task control, value, perceived performance, and actual performance outcomes on a diagnostic reasoning task with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 35 publications
9
30
0
3
Order By: Relevance
“…ALT is a broad term that includes a variety of sophisticated learning environments such Harley et al 2016a) and simulations or virtual worlds (BioWorld; Lajoie et al 2013;Jarrell et al 2016). Although the above labels for different types of learning environments are helpful for identifying specific features, they are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…ALT is a broad term that includes a variety of sophisticated learning environments such Harley et al 2016a) and simulations or virtual worlds (BioWorld; Lajoie et al 2013;Jarrell et al 2016). Although the above labels for different types of learning environments are helpful for identifying specific features, they are not mutually exclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Decomposing domain-specific problem-solving competence into various facets and, at the same time, providing an integrated measurement offers opportunities for a differentiated assessment of competence profiles and individualized interventions (Herl et al 1999;Sugrue 1995). We also postulated metacognitive facets of problem solving, which as yet have not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…'Embedded Experience Sampling' (EES) builds on the 'Experience Sampling Method' (ESM) introduced by Csikszentmihalyi and colleagues (Hektner et al 2007) and similar methods of data-collecting 'in situ' such as the 'Continuous State Sampling Method (CSSM)' introduced by Sembill and colleagues (2002). Test-takers are requested to stop at certain times during the test and spontaneously answer short prompts (EES items) regarding their actual experience of the problem situation.…”
Section: Implementation Of Eesmentioning
confidence: 99%
“…Contemporary research on the role of human emotions in educational settings have demonstrated that individuals can experience multiple and blended emotions simultaneously in an achievement context and this may have imperative impacts on their academic functioning and academic achievement [31][32][33]. In fact, Pekrun [1] recognized that multiple emotional experiences may co-occur in an achievement context, and that these mixed emotional experiences may reveal distinctive patterns of motivation and behavior.…”
Section: A Person-centered Perspective Of Achievement Emotionsmentioning
confidence: 99%
“…A study by Jarrell et al [32] investigated the relationship of the achievement emotions experienced by students during performing a task and their appraisals of task control, value, perceived performance, and actual performance on a diagnostic reasoning task with a Computer-based Learning Environment (CBLE), BioWorld. The sample of the study included 26 university medical students.…”
Section: Research On Achievement Emotions Using a Person-centered Permentioning
confidence: 99%